miR-378b Regulates Insulin Sensitivity by Targeting Insulin Receptor and p110α in Alcohol-Induced Hepatic Steatosis - Li, Yuan-yuan; Zhong, Yu-juan; Cheng, Qi; Wang, Ying-zhao; Fan, Yuan-yuan; Yang, Cheng-fang; Ma, Zuheng; Li, Yong-wen; Li, Li (Frontiers in Pharmacology, 2020)
Insulin resistance has been implicated in alcoholic liver disease. A previous study has shown that microRNAs (miRNAs) play a major role in the production, secretion, and function of insulin. MiRNAs are capable of repressing multiple target genes that in turn negatively regulate various physiological and pathological activities. However, current information on the biological function of miRNAs in insulin resistance is limited. The goal of the present study was to elucidate the role of miR-378b in alcohol-induced hepatic insulin resistance and its underlying mechanism. This study has observed that miR-378b is upregulated in NIAAA alcoholic mouse models as well as in ethanol-induced L-02 cells in vitro. Furthermore, miR-378b overexpression impaired the insulin signaling pathway, and inhibition of miR-378b improved insulin sensitivity in vivo and in vitro. A mechanistic study revealed that IR and p110α are direct targets of miR-378b. Together, these results suggest that miR-378b controls insulin sensitivity by targeting the insulin receptor (IR) as well as p110α and possibly plays an inhibitory role in the development of insulin resistance, thereby providing insights into the development of novel diagnostic and treatment methods.